Negative Regulation of Zap70 by Lck Forms the Mechanistic Basis of Differential Expression in CD4 and CD8 T Cells - Damen, Hassan; Tebid, Christian; Viens, Melissa; Roy, Denis-Claude; Dave, Vibhuti P. (Frontiers in Immunology, 2022)
Lck and Zap70, two non-receptor tyrosine kinases, play a crucial role in the regulation of membrane proximal TCR signaling critical for thymic selection, CD4/CD8 lineage choice and mature T cell function. Signal initiation upon TCR/CD3 and peptide/MHC interaction induces Lck-mediated phosphorylation of CD3 ITAMs. This is necessary for Zap70 recruitment and its phosphorylation by Lck leading to full Zap70 activation. In its native state Zap70 maintains a closed conformation creating an auto-inhibitory loop, which is relieved by Lck-mediated phosphorylation of Y315/Y319. Zap70 is differentially expressed in thymic subsets and mature T cells with CD8 T cells expressing the highest amount compared to CD4 T cells. However, the mechanistic basis of differential Zap70 expression in thymic subsets and mature T cells is not well understood. Here, we show that Zap70 is degraded relatively faster in DP and mature CD4 T cells compared to CD8 T cells, and inversely correlated with relative level of activated Zap70. Importantly, we found that Zap70 expression is negatively regulated by Lck activity: augmented Lck activity resulting in severe diminution in total Zap70. Moreover, Lck-mediated phosphorylation of Y315/Y319 was essential for Zap70 degradation. Together, these data shed light on the underlying mechanism of Lck-mediated differential modulation of Zap70 expression in thymic subsets and mature T cells.